A rapid and sensitive spectrophotometric method for the determination of benzoyl peroxide in wheat flour samples - Kraingkrai Ponhong (2018)
© 2015, Food and Drug Administration, Taiwan. Published by Elsevier Taiwan LLC. A simple, rapid, and sensitive spectrophotometric method for the determination of benzoyl peroxide (BPO) in wheat flour samples was developed. The detection principle is based on BPO reacted with 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) to obtain a blue-green colored product that was detected at 415 nm by spectrophotometry. The effect of factors influencing the color reaction was investigated. Under the selected conditions, the linear range for quantification of BPO was observed between 0.2-1.0 mg L-1with r2= 0.998. The limit of detection (LOD) was 0.025 mg L-1. The developed method obtained superior precision (relative standard deviation < 2%) using 11 repeatability at 0.2 mg L-1, 0.6 mg L-1, and 0.8 mg L-1. The proposed methodology was successfully applied to determine BPO in wheat flour samples.